A tracking mechanism using agents for personal mobility in IP networks - Hassan, Wan Haslina; Hassan Abdalla Hashim, Aisha; FIsal, Norsheila (IEEE, 2008)
This paper presents our ongoing work in developing an agent architecture to support personal mobility in IP networks. In particular, the paper discusses a tracking mechanism that facilitates location management using agents where both host and user mobility is accorded by the network. Towards this end, a multi-layered agent architecture is proposed and this acts as an overlay providing intelligence in an IP-based network. The agent messaging and collaboration provide the necessary signaling and control mechanism for tracking user movement across multiple domains. This represents a departure from traditional methods of providing mobility services where intelligence is normally restricted to end systems. Ultimately, the role of the collaborative agent architecture is to provide an IP-based network with the ability to exhibit dasiaintelligentpsila behaviour i.e. awareness, dynamism and adaptation, in terms of user movement and preferences.